The emergence of interior vowels and heterosyllabic vowel sequences in Ngwi (Bantu B861, DRC) - Pacchiarotti, Sara; Maselli, Lorenzo; Bostoen, Koen (Papers in Historical Phonology, 2021)
In this article, we offer a historical account of the development of two phonemic ‘interior’ vowels, [ə] and [ɤ], and heterosyllabic vowel sequences in Ngwi, a virtually undescribed West-Coastal Bantu language spoken in the western part of the Democratic Republic of the Congo. While interior vowels phonologized due to the loss of their conditioning environment, most heterosyllabic vowel sequences come from the fission of an erstwhile palatal on-glide diphthong, itself originating in a long [–high] vowel. This origin is exactly the opposite of what has been reported for other language families such as Romance, where certain heterosyllabic vowel sequences of the *iV type evolved into diphthongs. The Ngwi data also show that phonemic interior vowels exist in languages of the Niger-Congo phylum where they had not been reported before. The historical development of heterosyllabic vowel sequences in Ngwi might have parallels in several other Bantu languages from the wider Congo rainforest area, where phonetic and phonological documentation is still embryonic.